Setting up a new library and information service - Porter, Kirby; ScienceDirect eBooks (Witney : Chandos Publishing (Oxford) Ltd, 2003)
This book is intended as a guide for those people who have been charged with establishing a library or information service in their organisation. It is a practical guide to the steps that need to be taken, the people that will need to be dealt with and the procedures that will have to be adopted in order to bring the venture to a successful conclusion. The book contains many practical tips and hints from the author, based upon his 'hands-on', practical experience of setting up many new information services.
1. Why organisations need library and information services -- 2. First steps to getting started -- 3. The importance of customers in the planning and development of the new service -- 4. Managing access to your information -- classification -- 5. Managing access to your material -- cataloguing -- 6. Providing additional material for your users -- the art of stock selection -- 7. Planning further service development -- 8. Measuring the performance of the library service -- 9. Marketing the new service -- 10. Conclusion.
Includes bibliographical references and index.
Elsevier
Keywords: Information resources management; Library administration; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Information resources management; Library administration; Electronic books